A novel co-culture model of murine K12 osteosarcoma cells and S. aureus on common orthopedic implant materials: 'the race to the surface' studied in vitro. Issue 6 (2nd July 2016) - McConda, David B.; Karnes, Jonathan M.; Hamza, Therwa; Lindsey, Brock A.
Abstract: Infection is a major cause of orthopedic implant failure. There are few studies assessing both tissue cell and bacterial adherence on common orthopedic implant materials in a co-culture environment. An in vitro co-culture model was created using K12 osteosarcoma cells and Staphylococcus aureus in a medium incubated over metal disks for 48 h. The results showed that, in the presence of S. aureus, there were fewer osteosarcoma cells attached to the disks for all substrata tested. There were significantly more osteosarcoma cells adhering to the cobalt chrome than the stainless steel and titanium disks. Overall, in the presence of osteosarcoma cells, there were more bacteria adhering to the disks for all the substrata tested, with significantly more bacteria adhering to the stainless steel disks compared to cobalt chrome and titanium disks. Scanning electron microscopy verified that osteosarcoma cells and bacteria were adherent to the metal disks after incubation for 48 h. Furthermore, the observation that more bacteria were in the co-culture than in the control sample suggests that the osteosarcoma cells serve as a nutrient source for the bacteria. Future models assessing the interaction of osteogenic cells with bacteria on a substratum would be improved if the model accounted for the role of the immune system in secondary bone healing.